Types and Abundance of Phytoplankton in The Maninjau Lake, Tanjung Raya Sub–District, Agam District, Sumatera Barat Province - Meria Ulfa; Madju Siagian; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractManinjau Lake is a volcanic lake that is used for various human activities such as drink water sources, tourisms, transportation and aquaculture. Many activities contributes the input of organic and anorganic matters that affect water quality and the trophic state of the water in general. A research aims to understand the types and abundance of phytoplankton and the trophic state of the Maninjau Lake waters based on the Nygaard Index was conducted in January – March 2017. There were 4 stations namely Station 1 (bay area), Station 2 (inlet area), Station 3 (fish floating cages area) and Station 4 (outlet area). In each station, the water were sampled from 3 different depths, in the surface (0.5 m), 2 Secchi depth (1.2 m) and 4 Secchi depth (2.4 m). Samplings were conducted once/2 weeks for 1.5 month period. Results shown that there were 68 phytoplankton species that were belonged to six families, namely Bacillariophyceae (20 species), Chlorophyceae (29 species), Cyanophyceae (13 species), Euglenophyceae (2 species), Dinophyceae (1 species) and Chrysophyceae (3 species).The average of phytoplankton abundance was around 12,517 – 21,565 cells/L and the Nygaard Index value was 2.4 – 3.4. The water quality parameters were as follows: temperature 26.8 – 28.4 0C, transparency 53.67 – 72 cm, depth 16.9 – 47.5 m, pH 6 – 8, free CO27.3 – 32.7 mg/L, DO 0.24 – 8.09 mg/L, nitrate 0.02 – 0.39 mg/L and phosphate0.068 – 0.161 mg/L.Based on the abundance of phytoplankton and the Nygaard Index value, the Maninjau Lake can be categorized as mesotrophic to eutrophic. Keywords:Phytoplankton, Maninjau Lake, Indeks Nygaard, Water Quality